Bromocriptine and insulin sensitivity in lean and obese subjects. Issue 6 (November 2016) - Bahler, L; Verberne, H J; Brakema, E; Tepaske, R; Booij, J; Hoekstra, J B; Holleman, F
Abstract : Bromocriptine is a glucose-lowering drug, which was shown to be effective in obese subjects with insulin resistance. It is usually administered in the morning. The exact working mechanism of bromocriptine still has to be elucidated. Therefore, in this open-label randomized prospective cross-over mechanistic study, we assessed whether the timing of bromocriptine administration (morning vs evening) results in different effects and whether these effects differ between lean and obese subjects. We studied the effect of bromocriptine on insulin sensitivity in 8 lean and 8 overweight subjects using an oral glucose tolerance test. The subjects used bromocriptine in randomized cross-over order for 2 weeks in the morning and 2 weeks in the evening. We found that in lean subjects, bromocriptine administration in the evening resulted in a significantly higher post-prandial insulin sensitivity as compared with the pre-exposure visit (glucose area under the curve (AUC) 742 mmol/L * 120 min (695–818) vs 641 (504–750), P  = 0.036, AUC for insulin did not change, P  = 0.575). In obese subjects, both morning and evening administration of bromocriptine resulted in a significantly higher insulin sensitivity: morning administration in obese: insulin AUC (55, 900 mmol/L * 120 min (43, 236–96, 831) vs 36, 448 (25, 213–57, 711), P  = 0.012) and glucose AUC P  = 0.069; evening administration in obese: glucose AUC (735 mmol/L * 120 min (614–988) vs 644 (568–829), P  = 0.017) and insulin AUC, P  = 0.208. In conclusion, bromocriptine increases insulin sensitivity in both lean and obese subjects. In lean subjects, this effect only occurred when bromocriptine was administrated in the evening, whereas in the obese, insulin sensitivity increased independent of the timing of bromocriptine administration.